Perceptions, Attitudes, and Return Intentions in Nature-Based Tourism: Evidence from Generation Z at Crystal Cave Kupang City - Rie E. I. Nafie (Journal of Management and Business Innovation, 2026)
This study aims to examine the roles of destination perceptions and tourist attitudes in shaping revisit intentions among Generation Z at Cave Crystall Tourist Attraction in Kupang City, Indonesia. In addition, it seeks to investigate how digital information influences the formation of destination perceptions and revisit decisions in a nature-based tourism context. The study employs a quantitative research approach using a survey method targeting Generation Z tourists who had previously visited Cave Crystall. Data were collected through structured questionnaires and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). This study contributes to the tourism behavior literature by integrating digital information as an antecedent of destination perceptions and revisit intention within a Generation Z and nature-based tourism framework. The findings provide empirical evidence that digital information shapes destination perceptions and revisit intention, while tourist attitudes are more strongly influenced by direct destination experiences rather than digital exposure The findings offer practical insights for destination managers and policymakers to strengthen destination image management and enhance on-site tourism experiences to encourage repeat visits among Generation Z. Strategic use of digital platforms should focus on reinforcing positive destination perceptions, while experiential quality remains critical in shaping favorable tourist attitudes in nature-based tourism destinations. This study is limited to a single nature-based tourism destination and focuses exclusively on Generation Z visitors, which may restrict the generalizability of the findings. Future research is encouraged to examine different generational cohorts, expand to multiple destinations, and incorporate additional behavioral or experiential variables to further enrich the understanding of revisit intention in digital-era tourism.